Predictors of Portuguese teachers’ use of Information and Communication Technologies in literacy classes - Nunes, Andreia; Limpo, Teresa; Castro, São Luís (Frontiers in Psychology, 2022)
In the last years, the teaching and learning of literacy has changed due to the development of Information and Communication Technologies (ICT). The use of ICT in the classroom depends largely on teachers, who are the key players in its integration. However, several factors influence teachers’ decisions to use ICT in their classroom, both internal (e.g., self-efficacy) and external (e.g., school support). Indeed, despite the potential benefits of using ICT, not all teachers use them in their teaching practice. In the present study, we examined which are the main factors influencing teachers’ effective use of ICT in literacy classrooms. A total of 125 teachers lecturing Portuguese Language in grades 5-12 participated in this study (M = 50.00 years, SD = 7.88; 89% women). Teachers filled in an online survey, comprising sociodemographic questions (viz., age, gender, education, years of teaching experience, teaching level, school type, and geographical area) and four questionnaires related to ICT and teaching. Results showed that effective use of ICT was predicted by both internal (ICT’ self-efficacy and constructivist conception of teaching) and external (lack of access and support, and gatekeepers) factors. These findings may help in the identification of key targets to facilitate the effective use of ICT in literacy classrooms.